Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Supporting adaptive management. Monitoring and evaluation tools and approaches - Pasanen, Tiina; Barnett, Inka (ODI, 2019)
Key messages • This working paper introduces a set of monitoring and evaluation (M&E) tools and approaches, discussing their potential usefulness in supporting adaptive management in development and humanitarian programmes. It emphasises adaptive programmes characterised by complex aspects, such as: (1) they are innovative; (2) they have uncertain pathways for change; or (3) they operate in uncertain or unstable environments. • The majority of these tools have been used in international development for many years. However, adaptive management brings additional challenges for monitoring and evaluating programmes, as they require intentional M&E design from the start that is oriented towards both learning and accountability. • All of the tools and approaches introduced in this paper have potential to support learning and adaptation, although in various ways and at different stages of a programme. Some tools can support strategic planning and diagnosing throughout a programme – especially during design and inception – while others can help analyse causal relationships at specific points in a programme. It is important to tailor the approach used for its intended purpose. However, whether learning and adaptation happens depends also on factors other than the choice of M&E methods. • For some of these approaches a considerable body of evidence already exists but, for many, more practical examples and systematic analysis is needed. In addition to building the evidence base concerned with which approaches are suitable for different types of adaptive programmes and why, it is also important to improve understanding of the enabling environmental conditions necessary for the tools and approaches outlined here to facilitate and strengthen evaluative thinking, evidence-informed decision-making and ongoing programme iteration.